The study and conservation of the 20th century wooden chest and its Lepidoptera collection - Júlia Tauber (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
A carved wooden chest was recently given to the University of Lincoln for conservation treatment. The chest holds four drawers with a Lepidoptera (Butterflies and Moths) collection badly damaged by pests. After consultation, it has been decided that the Lepidoptera specimens will be restored, without modification or serious intervention. This was achieved after investigations were carried out on historic repairs on Lepidoptera collections, and consultation with entomologists as well. The research involved the examination of repairs carried out in the 18th century on butterflies at the Hunterian Museum’s collection. One drawer holding moths was treated and restored. Conservation treatment was also applied on the wooden chest.